ANALISIS VARIASI KOMPONEN FISIK ATLET BOLA BASKET MELALUI PENDEKATAN STATISTIK DESKRIPTIF DAN KATEGORI PERFORMANSI - Rizkanto, Billy Emir; Billy Emir; Raymond Ivano Avandi; Eka Kurnia Darisman; Bhekti Lestari (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2025)
This study aims to analyze variations in the physical fitness components of university-level basketball athletes using descriptive statistical analysis and performance categorization. Thirty-two athletes participated in the assessment, which included anthropometric measurements (age, height, body mass, and BMI) and physical fitness tests consisting of strength, endurance, speed, power, flexibility, and agility. The descriptive results showed that the athletes had an average age of 20.12 ± 1.15 years, height of 175.50 ± 8.34 cm, body mass of 73.34 ± 7.41 kg, and a BMI of 23.76 ± 1.17 kg/m², placing the majority within the normal weight category. Strength demonstrated a mean of 131.72 ± 9.06, indicating a moderate-to-good level of muscular capacity. Endurance averaged 40.82 ± 2.58, showing relatively stable aerobic performance across athletes. Speed over 20 meters recorded a mean of 3.34 ± 0.20 seconds, reflecting adequate sprint capability for university-level basketball players. Power exhibited higher variability, with a mean of 229.66 ± 19.70, suggesting differences in explosive performance. Flexibility displayed the widest range (M = 25.50 ± 29.25), indicating heterogeneous mobility levels among athletes. Agility showed a mean of 9.10 ± 0.53 seconds, consistent with typical agility performance at this competitive level. Overall, the descriptive findings highlight that the athletes fall predominantly within moderate performance categories across most components, although flexibility and power show substantial individual variability. These results suggest the need for more individualized training programs, especially targeting mobility and explosive strength. The study provides a comprehensive baseline profile to guide coaches in developing evidence-based conditioning strategies to enhance basketball-specific physical performance